PENINGKATAN KEMAMPUAN MENULIS SURAT RESMI SISWA KELAS VIII MTs ALKHAIRAAT SIBALAYA MELALUI STRATEGI TERBIMBING - Ferawati, Ferawati (BAHASANTODEA, 2015)
Abstract The Problem statement in this research was whether the application of guided strategies could improve the ability of students of the eight grade at MTs. Alkhairaat Silabaya in writing a formal letter. It was a classroom action research. The procedures for implementing the plan of action research: (1) planning action, (2) implementation of the action, (3) observation, (4) reflection. The research subjects were 20 students of class VIII MTs. Alkhairaat Sibalaya. The results of the research in the first cycle in pre writing stage was 69.9, in writing stage was 67.1 and the revision stage was 68,5. Furthermore, in the second cycle, the result of evaluation obtained 68.5. the second cycle, the results of the evaluation in pre writing stage was 100, in writing stage was 81.75 and revision stage was 84.75. Furthermore, the result of the second cycle was 88.83. Based on the data, it could be concluded that by using a guided strategy could improve the ability of students of class VIII MTs. Alkhairaat Silabaya in writing a formal letter. Developing the skill of students in writing a formal letter through guided strategies worth considering the subject of a class action research for the teachers and further research. Keyword: Writing Skills, Official Letters, and Guided Strategy.